Barreiras e nível de atividade física em idosos - RODRIGUES, Nildilene Pereira (2024)
The objective of the present study was to analyze the barriers to the practice of physical activity and the level of physical activity in elderly people in the city of Pinheiro-MA. The sample consisted of elderly men and women aged 60 years or over, residing in the urban area of the municipality of Pinheiro-MA, established through random sampling by conglomerates (residential households), collected from January to July 2023. The research investigated 305 elderly people, 193 women (63.3%) and 112 men (36.7%), with an average age of 70.8 ± 8.1 years. Levels of physical activity and barriers to practicing physical activity in the elderly were assessed, in which questionnaires were applied to obtain information regarding the sociodemographic and health profile; anthropometric data and indices; level of physical activity (IPAQ - short version) and barriers to activity (QBPAF). For data analysis, descriptive statistics were performed, using mean and frequency distribution with the help of Excel and SPSS statistical package version 27.0, with a significance level of 5%. Most elderly people were classified as physically inactive (84.2%) and active (15.8%). The main barriers reported by the elderly to the regular practice of physical activity were. I am afraid of getting hurt, falling or harming my health 121 (40.0%), I feel a lack of safety in the environment 107 (35.0%), already I am active enough 93 (30.5%). Regarding the least common barriers among the elderly, they were identified: I have urinary incontinence 10 (3.3%), I have had unpleasant experiences 12 (4.0%), I am too fat or too thin 15 (5.0%). The external and physical domains had lower scores, reporting a greater perception of barriers. A significant association was identified between the barriers of the elderly and the level of physical activity obtained through the chi-square test on the barriers: I have an illness, injury or disability (χ2 = 25.5; p = 0.013), my health is very bad (χ2 = 29.2; p = 0.004), I feel a lack of security in the environment (χ2 = 32.1; p = 0.001) and the climate is unfavorable (χ2 = 26.8; p = 0.008). IPB did not indicate a significant association with the level of physical activity (χ2 = 4.25; p = 0.642). Therefore, most elderly people were inactive, and this result is associated with the presence of different barriers to practicing physical activity.